Evaluating agreement between a high-g and low-g accelerometer for measuring tibial acceleration across a range of running velocities - Wong, J.; Wyatt, H. E.; Whatman, C.; Cross, M. R.; Yang, D.; Sheerin, K. (Sports Biomechanics, 2025)
Modern inertial measurement units house multiple accelerometers with differing specifications. Previous studies have used both high-g and low-g accelerometers to measure peak tibial acceleration (TA) during running. This dual approach may introduce inconsistencies with data processing due to the different specifications. The purpose of this study was to evaluate the agreement between the high-g and low-g accelerometers in measuring peak axial and resultant TA across a range of running velocities. One hundred recreational runners ran on an athletics track at five self-selected velocities, ranging from very slow to very fast based on their comfortable training pace. Results indicated the difference in agreement between the high-g and low-g accelerometers was curvilinear, with bias shifting towards the high-g accelerometer at higher TA magnitudes. However, the predicted difference was small, only exceeding ±1 g when measuring axial TA approaching its maximum range (16 g). Based on the comparable performance of the high-g and low-g accelerometers, and the relatively high frequency of data clipping in the low-g accelerometer (209 of 495 trials; 42%), it is recommended to use the high-g accelerometer exclusively for measuring TA during running, simplifying data collection and processing requirements.